Severe emm89 Group A Streptococcal Disease Characterized by Toxic Shock and Endocarditis - Morouge Alramadhan; Gloria P. Heresi; Anthony R. Flores (Case Reports in Infectious Diseases)
Invasive group A Streptococcus infections are associated with diverse presentations. We report a severe, rare case of GAS infection with dissemination including endocarditis and STSS. While whole genome sequencing of blood and pharyngeal isolates did not reveal any unique features attributable to the severe presentation, our approach serves as a template for investigation of severe manifestations of common infections.